The professionalism of social educator professional regulation front of education social: disputes around the project Law 5346/2009 - Pereira, Antonio (Faculdade de Ciências e Letras/Unesp, 2016)
The text analyzes the professionalism of the social educator front profissonal regulation of social education imposed by the Draft Law No. 5346/2009. Conceptualizes education and educators, actors such education and professionalism. Describes critically the dispute surrounding the said Project, which the National Congress, which has been the subject of intense debate and criticism among practitioners of social education so that many wish his retirement from Congress by misconceptions perpetrated by example, allow any other professional obtains registration, without necessarily proving tacit and formal educators who are handicapping thus building a professional identity that educational field. But, there is clarity and consensus among (the) many (as) teachers (as) organized social associations, as ABRAPSocial, AEESP and AEC, on other issues, such as the minimum qualification for the exercise if average or higher , amplicon or not the areas of professional activity, inclusion of social pedagogy in the professionalism of the (a) educator (a), amongst others. This PL is already the second replacement, and clearly, showing the strength of a decision of the Associations.